Posttraumatic Stress Symptoms, Quality of Life, and Stress Burden in Caregivers of Patients With Severe Mental Illness: An Underestimated Health Concern - Rady, Ahmed; Mouloukheya, Tarek; Gamal, Eman (Frontiers in Psychiatry, 2021)
Caregivers of patients with severe mental disorders experience a heavy stress burden that can manifest as psychiatric symptoms mimicking posttraumatic stress disorder (PTSD) and can negatively impact interpersonal relationships and work performance. The present study investigated the prevalence of PTSD symptoms, quality of life (QoL), and stress burden in caregivers of patients with severe mental illness. A total of 70 caregivers of severely mentally ill patients and 70 control subjects who were caregivers of patients with a chronic debilitating medical illness (cardiovascular disease) were recruited from university hospital outpatient facilities. Severe mental illness was defined based on a Global Assessment of Functioning score <50 and duration of illness >2 years. Both groups were evaluated with the Zarit Burden interview, a QoL questionnaire, and Posttraumatic Diagnostic Scale (PDS). The results showed that 37.14% (n = 26) of caregivers of patients with severe mental illness showed PTS symptoms compared to 0% of caregivers of patients with physical illness, and 15.17% (n = 11) met the diagnostic criteria for PTSD. Caregivers of patients with severe mental illness had higher stress burden and lower QoL scores than the control group (p < 0.05). These results indicate that caregivers of patients with severe mental illness have a high stress burden that may lead to PTSD, highlighting the importance of providing psychological support to this group.